Modulação da melatonina na expressão do NF-КB, no transcriptoma e metaboloma em modelos de câncer de mama e hepático - Paula Junior, Rubens de (2018)
Breast cancer is the most prevalent neoplasm in women and the subtype Triple Negative (TNBC) is one of the most serious because of its aggressive metabolic phenotype. Hepatocellular carcinoma (HCC) is the most common primary neoplasm in liver tissue and, together with breast neoplasms, leads to the causes of death associated with cancer worldwide. It is known that tumor behavior is influenced by the host local intrinsic inflammation in the tumor microenvironment, as well as, by the metabolism reprogramming. Immunological cells in the tumor microenvironment are modulate by cytokines and transcription factors such as NF-kB. In addition to inflammation, host metabolism is under the diurnal control, which can control circulating levels of amino acids thus making it an important target for cancer analysis. OBJECTIVES: To evaluate the effect of melatonin on the transcript profile, on the modulation of NF-kB in breast and hepatic cancer models as well as on the metabolic profile in plasma during a diurnal variation in breast cancer. MATERIALS AND METHODS: In vitro was used HepG2 and MDA-MB-231. In vivo the tumor was developed by implantation of MDA-MB-231 tumor cells in nude athymic female mice. Plasma samples were collected under strict conditions at eight times during a full day and the tumors were removed for gene expression, RNA sequencing and Mass Spectrometry. RESULTS: It was observed a reduction in tumor volume and the expression of NF-kB in the animals with breast cancer and treated with melatonin. On the other hand, melatonin increased the expression of NF-kB in hepatocarcinoma cells. In the mammary tumor, microenvironment melatonin increased the expression of the Tnfaip8l2 and Il1f6 genes, which are important in the local immune response. In plasma, among the 20 amino acids detected, 10 had similar behavior during the day. At most times of the day, animals with tumor had reduced plasma levels of these amino acids. In addition, there was an inversion in the profile of these amino acids between the groups observed in the first hours of the morning. CONCLUSIONS: The effect of melatonin on NF-kB in breast cancer appears to be better defined, but in liver cancer its role remains controversial. In the same way the anti-tumor action of melatonin was proven by the high expression of the Tnfaip8l2 and Il1f6 genes in the tumor microenvironment. In the plasma samples, the changes in metabolites are a reflex of the altered metabolism, determined by mammary tumor cells in the mice background. While this inversion of the amino acid profile in animals suggests that one cyclic event of host metabolism at these times appears to influence circulating amino acid levels. Thus, our results have pointed out that during carcinogenesis there is a strong association between the immune response and the chronobiology of the host that requires further investigations.